Natural gas accumulation conditions and exploration prospects of the Middle Permian Qixia Formation in the Sichuan Basin - Zhang, Ya; Chen, Shuangling; Wen, Long; Zhang, Benjian; Wang, Hua; Xiao, Di; Xie, Chen; Zhang, Xiaoli; Quan, Li; Liu, Ran; Qiao, Yanping; Wang, Guangwei (Frontiers in Earth Science, 2022)
Exploration of natural gases in the Middle Permian Qixia Formation has achieved a breakthrough in the central and western Sichuan Basin since 2010. This study discusses the quality of dolomite reservoirs and source rocks, trap types and hydrocarbon charging history and proposes that good accumulation conditions are the basis for the large-scale enrichment of natural gas in the Qixia Formation. The high-quality reservoirs in the Qixia Formation are dolomites that primarily occur along platform margins and in the inner-platform shoals surrounding the Caledonian palaeo-uplifts. The Qixia gases originated mainly from the Cambrian and Permian mudstone source rocks. The overlaying Permian source rocks and the underlying Cambrian source rocks are both widely distributed and could provide sufficient gases for dolomite reservoirs. Additionally, the structural or structural-lithologic traps formed by an overlap of the Qixia dolomites and structurally high are favourable for oil and gas accumulation. The Qixia Formation had experienced four episodes of oil and gas charging from the middle-late Triassic to the Early Cretaceous, and traps located in structural-high zones are most favourable for hydrocarbon accumulation. Thus, the Qixia Formation has excellent accumulation conditions for the formation of large-scale gas fields. The concealed structural belts in the footwall of fault No. 1, the Longmenshan–Daxingchang structural belts and the periphery Gaomo–Shehong palaeo-uplift are the key zones for large-scale gas exploration in the Qixia Formation. The Qixia Formation is an important strategic replacement field for natural gas exploration in the Sichuan Basin following the Ediacaran Dengying Formation and the Cambrian Longwangmiao Formation.